A phase I oncolytic virus trial with vesicular stomatitis virus expressing human interferon beta and tyrosinase related protein 1 administered intratumorally and intravenously in uveal melanoma: safety, efficacy, and T cell responses - Smith, Katherine E. R.; Peng, Kah-Whye; Pulido, Jose S.; Weisbrod, Adam J.; Strand, Carrie A.; Allred, Jacob B.; Newsom, Alysha N.; Zhang, Lianwen; Packiriswamy, Nandakumar; Kottke, Timothy; Tonne, Jason M.; Moore, Madelyn; et al. (Frontiers in Immunology, 2023)
Introduction: Metastatic uveal melanoma (MUM) has a poor prognosis with limited treatment options. These patients do not typically experience durable responses to immunotherapy with immune checkpoint inhibitors (ICIs) and their treatment options remain limited. Oncolytic viruses (OV) represent a novel approach to immunotherapy. Methods: We developed an OV with a Vesicular Stomatitis Virus (VSV) vector modified to express interferon-beta (IFN-β) and Tyrosinase Related Protein 1 (TYRP1) (VSV-IFNβ-TYRP1), and conducted a Phase 1 clinical trial with a 3+3 design in patients with MUM. VSV-IFNβ-TYRP1 was injected into a liver metastasis, then administered on the same day as a single intravenous (IV) infusion. The primary objective was safety. Efficacy was a secondary objective.Results: 12 patients with previously treated MUM were enrolled. Median follow up was 19.1 months. 4 dose levels (DLs) were evaluated. One patient at DL4 experienced dose limiting toxicities (DLTs), 2 This is a provisional file, not the final typeset article including decreased platelet count (grade 3), increased aspartate aminotransferase (AST), and cytokine release syndrome (CRS). 4 patients had stable disease (SD) and 8 patients had progressive disease (PD). Interferon gamma (IFNγ) ELIspot data showed that more patients developed a T cell response to virus encoded TYRP1 at higher DLs, and a subset of patients also had a response to other melanoma antigens, including gp100, suggesting epitope spreading. 3 patients with response to additional melanoma antigens were next treated with ICIs and 2 of these patients experienced durable responses.Discussion: Our study found that VSV-IFNβ -TYRP1 can be safely administered via intratumoral (IT) and IV routes in a previously treated population of MUM patients. Although there were no clear objective radiographic responses to VSV-IFNβ-TYRP1, dose-dependent immunogenicity to TYRP1 and other melanoma antigens was seen.